2008
DOI: 10.1111/j.1365-4632.2008.03796.x
|View full text |Cite
|
Sign up to set email alerts
|

Nail changes in pemphigus vulgaris

Abstract: Nail changes in PV are common and related to the number of skin bullae and the presence of periungual bullae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 18 publications
2
25
1
2
Order By: Relevance
“…PV'de tırnak tutulumu akut ve kronik paronişi, onikomadezis, Beau çizgileri, subungual hemoraji, subungual hiperkeratoz, trakionişi, pitting, sarı renk değişikliği ve onikolizis şeklinde görülebilir. PV'de paronişi ve onikomadezis en sık saptanan tırnak bulgularıdır 10 . PV'li olgularımızın %11,4'ünde onikomadezis mevcuttu.…”
Section: Discussionunclassified
“…PV'de tırnak tutulumu akut ve kronik paronişi, onikomadezis, Beau çizgileri, subungual hemoraji, subungual hiperkeratoz, trakionişi, pitting, sarı renk değişikliği ve onikolizis şeklinde görülebilir. PV'de paronişi ve onikomadezis en sık saptanan tırnak bulgularıdır 10 . PV'li olgularımızın %11,4'ünde onikomadezis mevcuttu.…”
Section: Discussionunclassified
“…Nail involvement in pemphigus vulgaris (PV) is not rare. Paronychia is the most common nail manifestation of PV, although discoloration of the nail plate, Beau's lines, severe nail dystrophy, onychomadesis (nail shedding), and even total destruction of the nail plate can occur (74)(75)(76)(77). Nail changes occasionally precede skin findings and often relapse just before generalized disease exacerbation (73).…”
Section: Nail Involvement In Autoimmune Bullous Disordersmentioning
confidence: 99%
“…A recent prospective study involving 79 patients with PV showed nail changes in 34.2% of the patients (72). Subungual bullae are often hemorrhagic and can cause nail bed detachment leading to onycholysis, subungual hemorrhages, and subungual hyperkeratosis (77,78). Severe nail changes are often associated with extensive and severe skin involvement.…”
Section: Nail Involvement In Autoimmune Bullous Disordersmentioning
confidence: 99%
“…Pseudopyogenic granuloma of the proximal or lateral nail fold can also be seen, and it has been reported to be the first symptom of a relapse of the disease [20]. According to Habibi et al [21], these nail changes are related to the number of skin bullae and the presence of periungual bullae. Depending on the location of acantholysis in the nail folds, different nail changes may result.…”
Section: Discussionmentioning
confidence: 99%
“…Nail matrix damage as a result of periungual inflammation results in Beau's lines, onychomadesis, onychoschizia, cross-ridging, pitting, and trachyonychia. Habibi et al [21] noted these signs in one-third of patients with PV. Subungual bullae cause nail bed detachment with onycholysis, which is often hemorrhagic and heralds a poor prognosis in patients with PV [22].…”
Section: Discussionmentioning
confidence: 99%